ACCELERATE STUNTING REDUCTION THROUGH THE ROLE OF RELIGIOUS INSTITUTIONS WITH AN ENVIRONMENTAL PURPOSE APPROACH TO RISK GROUPS - Rojali, Rojali; Arif Sumantri; Masri Mansoer; Usep Abdul Matin (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
The availability of quality human resources determines the progress of a nation because by having quality human resources, a nation will be able to use and develop the latest technology to increase productivity on all fronts to realize the nation's prosperity. To achieve this, Indonesia is faced with an urgent problem to solve, namely stunting. The Indonesian government is aware of these problems and has taken several steps to solve them holistically by involving various approaches. However, there is no role model for religious institutions to accelerate the reduction of stunting prevalence in Indonesia. From this problem, the research design aims to build a model of the Islamic approach and environmental piety in increasing the convergence of accelerating stunting reduction in the community, as well as developing a model for accelerating stunting reduction through proper clean water and safe sanitation. The research design presented is expected to be material for joint discussion to contribute to improving the quality of human resources, Primarily by reducing the prevalence of stunting.